2019
DOI: 10.1002/jsc.2302
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the choice of interaction after the international joint venture termination in Africa: Total interpretive structural modeling

Abstract: The choice of interaction after the international joint venture (IJV) termination is influenced by different factors in varying levels that can be hierarchically depicted. On IJV termination, parent firms are deprived of value created during IJV. Parent firms can attempt to create a whole or part of the value created during IJV through an interaction post IJV termination. This study attempts to identify factors that influence the choice of interaction post IJV termination and categorize them hierarchically bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Leischnig and Geigenmuller (2018) drew on configuration theory to investigate the alliance proactiveness´ performance effects within the broader context of the firm and its market environment, while Yang and Meyer (2019) suggested that alliance proactiveness enables firms to react faster to new opportunities, achieving early mover advantages. Parameswar and Dhir (2019) analyzed which factors influence the decision to interact post international joint venture termination in Africa, whereas Kim (2019) showed the moderating effects on the relationship between R&D expenditure and liability and innovativeness performance. Despite these considerations, the links between autonomy (Gil-López et al , 2020), EO (Chen and Wang, 2020; Godley and Hamilton, 2020; Li et al , 2017; Oliveira Junior et al , 2016; Seo, 2020; Tokman et al , 2020), CA (Oliveira Junior, 2015), MO (Tjahjadi et al , 2020) and PT have received little attention (Baker and Sinkula, 2009; Teng, 2005; Wales et al , 2011).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Leischnig and Geigenmuller (2018) drew on configuration theory to investigate the alliance proactiveness´ performance effects within the broader context of the firm and its market environment, while Yang and Meyer (2019) suggested that alliance proactiveness enables firms to react faster to new opportunities, achieving early mover advantages. Parameswar and Dhir (2019) analyzed which factors influence the decision to interact post international joint venture termination in Africa, whereas Kim (2019) showed the moderating effects on the relationship between R&D expenditure and liability and innovativeness performance. Despite these considerations, the links between autonomy (Gil-López et al , 2020), EO (Chen and Wang, 2020; Godley and Hamilton, 2020; Li et al , 2017; Oliveira Junior et al , 2016; Seo, 2020; Tokman et al , 2020), CA (Oliveira Junior, 2015), MO (Tjahjadi et al , 2020) and PT have received little attention (Baker and Sinkula, 2009; Teng, 2005; Wales et al , 2011).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…The framework proposed here, finally, extends the scope of the alliance termination literature to the post-alliance termination phase, which is also as yet underexplored. Studies on alliance termination must investigate the influence of alliance termination on the actions and consequences of the post-termination phase (Parameswar et al , 2020b; Parameswar and Dhir, 2019b). This is an important aspect that cannot be overlooked because organizations involved in an alliance must bear the consequences of the termination in their individual functioning and in the future interactions between the parent firms of the terminated alliance.…”
Section: Future Research Agendamentioning
confidence: 99%
“…This strategic process helps companies to increase market share and competitive advantage without creating another business unit (Trautwein, 1990). In the globalization age, organizations are using strategic arrangements such as alliance (Etemad, Wright, & Dana, 2001; Holtbrügge, 2004), joint ventures (Parameswar & Dhir, 2019), and acquisitions to sustain in the changing competitive market (Dyer & Singh, 1998; Holtbrügge & Baron, 2013; Ireland, Hitt, & Vaidyanath, 2002). The cross‐border acquisition process has been widely used to gain access to new markets (Dhir & Sushil, 2017; Neary, 2007).…”
Section: Related Theoretical Backgroundmentioning
confidence: 99%